2017
DOI: 10.6026/97320630013214
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis study to evaluate the association of MTHFR C677T polymorphism with risk of ischemic stroke

Abstract: Ischemic stroke is a condition characterized by reduced blood supply to part of the brain, initiating the ischemic cascade, leading to dysfunction of the brain tissue in that area. It is one of the leading causes of death and disability and is estimated to cause around 5.7 million deaths worldwide. Methyl tetra hydro-folate reductase (MTHFR) is a rate limiting enzyme in the methyl cycle which catalyzes the only biochemical reaction which produces 5, Methyl tetra hydro folate, the co-substrate for the re-methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
11
0
3
Order By: Relevance
“…However, Cui showed the association between this polymorphism and adult IS in Asians and Caucasians, but not in Africans [ 34 ]. Abhinand et al analyzed 72 studies and found that this polymorphism may lead to a 1.3-fold increased risk of IS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Cui showed the association between this polymorphism and adult IS in Asians and Caucasians, but not in Africans [ 34 ]. Abhinand et al analyzed 72 studies and found that this polymorphism may lead to a 1.3-fold increased risk of IS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…В одном из мета-анализов показано, что вариант MTHFR 677 C→T ассоциирован с большим риском развития ишемического инсульта в регионах с низких потреблением фолатов (ОШ 1,68; 95% ДИ 1,44-1,97), чем в регионах с высоким уровнем потребления фолатов (ОШ 1,03; 95% ДИ 0,84-1,25). По данным одного из последних мета-анализов, включавшего 72 исследования с 12 390 пациентами с ишемическим инсультом и 16 274 пациентами в группе контроля, наличие генетического полиморфизма C667T повышало риск развития ишемического инсульта на 30% [16].…”
Section: îáñóAeäåíèåunclassified
“…N-5, N-10-methylenetetrahydrofolate reductase (MTHFR) is the rate limiting enzyme in the metabolism of Hcy. Studies have found that MTHFR has a certain correlation with cerebrovascular disease [1,2] and has a predictive value in ischemic stroke [25]. However, the relationship between MTHFR gene C677T polymorphism and WML is still unclear.…”
Section: Introductionmentioning
confidence: 99%